2016
DOI: 10.1123/jpah.2014-0601
|View full text |Cite
|
Sign up to set email alerts
|

On Your Mark, Get Set, Go: Levels of Physical Activity in the Kingdom of Saudi Arabia, 2013

Abstract: We found very low levels of physical activity in KSA. Perhaps, KSA can challenge communities or employers to devise solutions and reward those with the best results. These solutions would be of great value to other Gulf countries, as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…Such recent changes are applauded, especially when the national prevalence of no or insufficient physical activity among Saudi women was reported to be nearly 78%. 15 , 16 Similar figures among female youths were reported. 17 , 18 The high inactivity level among Saudi females coupled with high screen time represents a double burden on the health of young Saudi women.…”
Section: Introductionsupporting
confidence: 71%
“…Such recent changes are applauded, especially when the national prevalence of no or insufficient physical activity among Saudi women was reported to be nearly 78%. 15 , 16 Similar figures among female youths were reported. 17 , 18 The high inactivity level among Saudi females coupled with high screen time represents a double burden on the health of young Saudi women.…”
Section: Introductionsupporting
confidence: 71%
“…In a national survey, only 12% of the total Saudi population met the guidelines for physical exercise. 12 Since a sedentary lifestyle is common outside of pregnancy, it is likely that women remain sedentary during pregnancy. Other studies show that women are more likely to decrease exercise time than they are to initiate exercise during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…11 Further, available data on women in Saudi Arabia suggest that physical exercise is generally uncommon. It was reported that 75% of women have a sedentary lifestyle, 12 but physical exercise during pregnancy among Saudi women has not yet been reported. Since physical exercise is not part of the culture in general, 13 we hypothesized that the knowledge about the recommendations for exercise during pregnancy would be low and that there may be misconceptions that exercise during pregnancy poses health risks to the mother and the baby.…”
mentioning
confidence: 99%
“…Several studies have shown that obesity has rapidly increased in the region during the time period of this study (Mokdad et al 2014 , 2016 ). The studies have shown that inadequate physical activity and high body mass index are common in the region (El Bcheraoui et al 2016 ). Moreover, dietary factors are among the major risk factors for diabetes and CKD (Moradi-Lakeh et al 2016b ; Yakoob et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%